2021
DOI: 10.1049/cim2.12022
|View full text |Cite
|
Sign up to set email alerts
|

A quantum‐based diagnostics approach for additive manufacturing machine

Abstract: Current Additive Manufacturing machines have limited techniques to observe process conditions and to decrease process errors. In order to overcome these limitations and increase the level and accuracy of machine intelligence, machine conditions need to be monitored more meticulously. A novel method for the condition monitoring of a 3Dprinter is proposed in this paper. Quantum support vector machine (QSVM) is compiled for recognizing the health condition of the 3D-printer. The proposed quantum machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Many research communities [5,6,40] performed security tests and detailed analysis under the realistic scenarios, and concluded that source characteristics such as single or entangled photons are one of the performance deciding factor for any quantum-cryptography system. Quantum key distribution was first implemented in 1992 [1] and desired improvements were developed in [16-18, 20, 40].Quantum technologies are nowadays being deployed in many industrial applications [25]. Wavelength at 1550 nm is the desired one for practical deployment of quantum communication, as it provides less losses (0.2 dB/km) as compared to 1300 nm wavelength which offers higher losses (0.35 dB/km).…”
Section: Introductionmentioning
confidence: 99%
“…Many research communities [5,6,40] performed security tests and detailed analysis under the realistic scenarios, and concluded that source characteristics such as single or entangled photons are one of the performance deciding factor for any quantum-cryptography system. Quantum key distribution was first implemented in 1992 [1] and desired improvements were developed in [16-18, 20, 40].Quantum technologies are nowadays being deployed in many industrial applications [25]. Wavelength at 1550 nm is the desired one for practical deployment of quantum communication, as it provides less losses (0.2 dB/km) as compared to 1300 nm wavelength which offers higher losses (0.35 dB/km).…”
Section: Introductionmentioning
confidence: 99%